Features of the territorial planning of the sea coastal zone - Viktoria Yavorska; Antonina Shashero; Kateryna Kolomiyets; Olena Nikolayeva (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
The coastal zone in Ukraine is likely to undergo the most profound change in the near future. Already more than 65 percent of the Ukrainian Black Sea region population lives within 30 km of the coast. Consequently, unless territory planning and careful environmental management are instituted, sharp conflicts over coastal space and resource are likely, and the degradation of natural resources will stop future social-economic development. In order to maintain and restore coastal ecosystem it was implemented law about formation of the national ecological network of Ukraine. Later were developed General Scheme for Planning of the Territory of Ukraine and regional level planning scheme but there is no especial document regulating the use of land in the coastal zone. The study of geographical conditions, economic activity, and population resettlement shows separation within the regions of several echelons of economic development in relation to the coastline. Such separation may be based on differences in intensity and types of economic use within the territory and the water area, as well as the population density on the land. These features include the following economic stripes: seaside-facade, middle, peripheral – on land, and coastal, territorial waters, exclusive economic zone – in the direction of the sea. At the same time, each economic stripe has a complex internal structure. There are several basic principles of functional zoning of the territory highlighted in the article can help to rational plan the seaside regions.